Mental health literacy among basic healthcare providers and community health volunteers of Lalitpur Metropolitan City, Nepal - Prashabdhi Shakya; Anisha Chalise; Dhurba Khatri; Sujan Poudel; Shishir Paudel (BMC Health Services Research)
Abstract Background Mental health literacy (MHL) is particularly essential for primary healthcare providers for the early recognition and management of mental disorders. In Nepal, mid-level healthcare workers and Female Community Health Volunteers (FCHVs) play a vital role in community-based mental health services, yet their MHL remains insufficiently studied. This study assesses MHL among basic healthcare providers and health volunteers in Lalitpur Metropolitan City, Nepal and identifies factors associated with it. Methods A cross-sectional study was conducted among 233 healthcare workers, including mid-level healthcare providers, FCHVs, and other community health volunteers. Participants were selected through simple random sampling. MHL was measured using the Mental Health Literacy Assessment Scale (MHLAS), with scores dichotomized at the median (≥ 75 = high MHL, < 75 = low MHL). Descriptive statistics summarized key variables, while Pearson’s chi-square test and odds ratios (OR) with 95% confidence intervals (CI) were used to identify associations. Results The MHLAS score ranged between 45 and 98, with a mean score of 76 ± 9.27 and a median of 75 (IQR: 11). Out of 233 participants, 129 (55%; 95% CI: 49–62%) were classified as having high MHL. Higher education levels (OR = 9.77, p < 0.001) and mid-level healthcare provider status (OR = 2.44, p = 0.020) were significantly associated with higher MHL. Participants with 5–10 years of experience (OR = 4.50, p = 0.029) and those who received mental health training during academic courses (OR = 1.99, p = 0.022) or on the job (OR = 1.90, p = 0.036) had significantly higher MHL. However, factors such as gender, marital status, and work experience beyond 10 years were not significantly associated with MHL. Conclusion Despite their critical role in community mental health, nearly half of the primary healthcare providers in Nepal had low MHL. This study highlights the urgent need to integrate MHL training into academic curricula and ensure continuous professional development among basic health care providers.